PENINGKATAN HASIL BELAJAR SISWA PADA MATERI ASAMDAN BASA MELALUI MODEL PEMBELAJARAN INQUIRY BASED LEARNING (IBL) DI KELAS XI MIPA-5 SMAS DARUSSA’ADAH GLUMPANG TIGA - Kasmadi Kasmadi (Education Enthusiast : Jurnal Pendidikan dan Keguruan, 2021)
Classroom action research with the title "Improving Student Learning Outcomes on Acids and Bases Through Inquiry Based Learning (IBL) Learning Model in class XI MIPA-5 SMAS Darussa'adah Glumpang Tiga" was carried out with the background of student learning outcomes in class XI MIPA-5 in Acid and Base materials are still low. This study uses a descriptive approach with the type of Classroom Action Research (CAR). The data sources were students of class XI MIPA-5 SMA Darussa'adah Glumpang Tiga years which collected 19 students. The criteria for each action consist of Process Criteria and Outcomes Criteria. The process criteria are achieved if the result of the student's action observation score is 85% and the result criterion is achieved if 85% of the students get a score of 75 on the final action test. From the processing results, classical student learning outcomes have increased respectively by 42.11% and 21.05% with the percentage of completeness from 26.31% in the initial test, 68.42% in the first cycle, and to 89.47% in cycle II. The activity of teachers and students in learning by applying the Inquiry-Based Learning model has increased. Teacher activity increased by 16% from 77.33% to 93.33%, while student activity increased by 13.34% from 73.33% to 86.67%. Based on the results of the analysis, it can be applied Inquiry Based Learning to improve student learning outcomes on Acids and Bases in Class XI MIPA-5 SMA Darussa'adah Glumpang Tiga, and can increase the activity of teachers and students in learning by applying the Inquiry Based Learning (IBL) modelKeywords : Learning outcomes, Inquiry Based Learning (IBL) model